The tumor microenvironment: adding pieces to the puzzle - Aguilar-Cazares, Dolores; Perez-Medina, Mario; Benito-Lopez, Jesus J.; Galicia-Velasco, Miriam; Meneses-Flores, Manuel; Camarena, Angel; Lopez-Gonzalez, Jose S. (Frontiers in Immunology, 2026)
In the tumor microenvironment, malignant cells coexist and interact with each other and with stromal, immune, and endothelial cells, as well as with extracellular matrix proteins. The interaction occurs through membrane contact or the production of multiple soluble factors. The composition of tumor and matrix cells changes continuously during tumor development, along with the infiltration of immune cells, forming heterogeneous niches that vary in space and time. We integrate current knowledge about the complex interaction between heterogeneous cell populations in the TME and the impact of these networks in supporting immune defense, which paradoxically promotes tumor progression. We summarize the involvement of immune cells and highlight the impact of certain homeostatic processes mediated by stromal cell populations and matrix components on tumor development. We propose the role of metabolic reprogramming and oxidative stress, as well as extracellular vesicle-mediated signaling, in conferring tumor resistance and therapeutic strategies to disrupt pro-tumor communication networks while enhancing anti-tumor immunity. Our goal is to provide a comprehensive framework for understanding and addressing the cellular interactions underlying cancer progression, fostering opportunities to formulate strategies that control tumor growth and eliminate resistance to treatment options. This integrative perspective provides a basis for designing multi-targeted immunotherapies aimed at rewiring pro-tumor communication networks.